Smart automated fruit freshness recognition system using image processing and deep learning - Shil, Prantha; Rahman, Zisanur; Bin Jalil, Jawad; Bin Sakib, Kazi Rishad; Hossain, Md. Tamim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.